Post-glacial Chironomidae population responses to climate-driven variations in lake production in the Canadian Arctic Archipelago - Fortin, Marie-Claude (University of Ottawa (Canada), 2010)
The purpose of this thesis was to study long-term climatic variations and their impacts on aquatic ecosystem functioning in the Canadian Arctic. Sub-fossil remains of chironomids preserved in lacustrine sediment cores, and the organic, biogenic silica and carbonate fraction of the sediment matrix were analyzed to infer past lake production and provide new evidence of the impact of past climate changes in the Arctic. The modern relationship between chironomids, biological production indices and the physical environment was studied to permit the interpretation and quantification of past conditions from sediment cores. Bedrock composition exerts a very strong influence on sediment organic, biogenic silica and carbonate content of lake sediments, and an inference model for reconstructing lake water pH based on these parameters was developed. July air temperatures also affect aquatic and terrestrial production in the Arctic, but this effect is secondary to the effect of nutrient input. An inference model for reconstructing past mean July air temperatures based on the chironomid assemblages was developed using 88 Arctic lakes, and further improved by combining it with previously published data from across North America. A new inference model for July air temperatures, based on 379 Arctic and Boreal lakes was developed. This training set was based on sites covering a large temperature gradient (2°-16.6°C) and containing a great diversity of chironomid assemblages, making it appropriate for reconstructing past July air temperatures for Arctic and boreal lakes. Holocene climatic conditions were evaluated for the Arctic at Lake WB02 (Northern Victoria Island), Lake KR02 (Western Victoria Island) and Lake JR01 (Boothia Peninsula). Prior to ∼6.5-5.5ka the Arctic was relatively warm, and overall lake production was high. Mean July air temperatures remained colder during the mid- to late-Holocene until -1.0ka, when temperatures again cooled rapidly during the Little Ice Age. A recent (last 150 years) warming is seen at all three lakes as primary and chironomid production increased. At all locations, however, inferred temperatures for the last 150 years remain up to 2-3°C cooler than those inferred for the early Holocene.
Keywords: Climate Change.; Paleoclimate Science.; Biology, Limnology.